Peningkatan Keputusan Pembelian Melalui Celebrity Endorsement, Kualitas Produk dan Citra Merek - Yusuf Yusuf; Aprilia Attika Tiauw; Mohammad Amin; Hastuti Mustamin (Journal of Technopreneurship on Economics and Business Review, 2021)
This study aims to determine the effect of celebrity endorsement, product quality and brand image on purchasing decisions. Respondents of this research are customers of Beauty store at Kendari who buy and use Scarlett Handbody products totaling 110 samples. Multiple linear regression analysis was used to analyze the data in this study. The results showed that purchasing decisions were significantly influenced by celebrity endorsement, product quality and brand image. This study also found that brand image has the strongest role in influencing the purchasing decision of scarlet handbody.